GEORGIAN-IRANIAN RELATIONS IN THE POST-SOVIET PERIOD - TER-OGANOV, Nugzar (CENTRAL ASIA AND THE CAUCASUS, 2004)
From time immemorial, the diversity of Georgian Iranian relations has been expressed not only in wars and victories, but also in close trade and economic relations and in cultural interaction, including in the linguistic sphere. Despite the fact that contacts between these peoples were overshadowed by the cruelty of Aga Mohammad-khan Kajar, who in May 1795, plundered and destroyed Tbilisi, the Georgians, with their characteristic tolerance, bore no malice to the Iranians as a whole. In 1801, Georgia joined Russia, as a result of which bilateral Georgian Iranian relations were interrupted for essentially 200 years. Only after the collapse of the Soviet Union in 1991 and the formation of an independent Georgia did the opportunity present itself to think about restoring former contacts. The initiator of this process was the Islamic Republic of Iran (IRI). It was among the first states to officially recognize Georgia’s independence. (It should be noted that on the eve of the U.S.S.R.’s collapse, the Soviet press scared Georgia, Armenia, and Azerbaijan striving to achieve the national independence with the likelihood of an Iranian threat.1) Among other things, Iran recognized Georgia’s territorial integrity, which laid the foundation for a constructive dialog. At the first stage, contacts were established in the trade and economic sphere, which in the situation in which Georgia found itself was the most urgent problem. For example, in 1992, the first IRI industrial trade fair was held in Tbilisi, and Georgia took part in the traditional International Industrial Fair organized in Tehran. Then improvements were designated in the development of cultural relations, which was expressed in an increase in the number of exchange visits and in the rank of their participants. It should be noted that these states do not have any territorial claims against each other or disputed political interests, that is, even “at the outset” relations between them can be considered “cloudless,”2 and there are also good prerequisites for the further development of cooperation. A significant milestone in the history of bilateral relations was the visit by then Georgian president Eduard Shevardnadze to Iran at the beginning of 1993. The documents signed during this visit formed a legal foundation on which further development of Georgian Iranian cooperation was based. Quite a large role in this was played by the meeting between Eduard Shevardnadze (when he was U.S.S.R. foreign minister) and leader of the Islamic revolution Ayatollah Rukholla Khomeini, which took place several years prior to this.3